Themes with a difference : 228 new activities for young children - Green, Moira D. (Albany : Delmar, 1998)
Fat-tastic. Fabulous fungi. Shadow shenanigans. Marvelous motion. Magnificent magnifiers. Outer space. Fluid forms. The five senses. Tater time. Color capers. Soap science.
Keywords: Education; Activity programs; Early childhood education; Science -- Study and teaching (Early childhood); Education -- Early childhood education -- Activity programs